Apnoeic oxygenation during paediatric intubation: A systematic review - George, Shane; Wilson, Megan; Humphreys, Susan; Gibbons, Kristen; Long, Elliot; Schibler, Andreas (Frontiers in Pediatrics, 2022)
Objective This review assesses the effect of apnoeic oxygenation during paediatric intubation on rates of hypoxaemia, successful intubation on the first attempt and other adverse events. Data Sources The databases searched included PubMed, Medline, CINAHL, EMBASE and The Cochrane Library. An electronic search for unpublished studies was also performed. Study Selection We screened studies that include children undergoing intubation, studies that evaluate the use of apnoeic oxygenation by any method or device with outcomes of hypoxaemia, intubation outcome and adverse events were eligible for inclusion. Data Extraction Screening, risk of bias, quality of evidence and data extraction was performed by two independent reviewers, with conflicts resolved by a third reviewer where consensus could not be reached. Data Synthesis From 362 screened studies, fourteen studies (N = 2442) met the eligibility criteria. Randomised controlled trials (N=482) and studies performed in the operating theatre (N=835) favoured the use of apnoeic oxygenation with a reduced incidence of hypoxaemia (RR 0.34, 95% CI 0.24 to 0.47, p<0.001, I2= 0% and RR 0.27, 95% CI 0.11 to 0.68, p = 0.005, I2= 68% respectively). Studies in the ED and PICU were of lower methodological quality, displaying heterogeneity in their results and were unsuitable for meta-analysis. Among the studies reporting first attempt intubation success, there were inconsistent effects reported and data were not suitable for meta-analysis. Conclusion: There is a growing body of evidence to support the use of apnoeic oxygenation during the intubation of children. Further research is required to determine optimal flow rates and delivery technique. The use of humidified high-flow oxygen shows promise as an effective technique based on data in the operating theatre, however its efficacy has not been shown to be superior to low flow oxygen in either the elective anesthetic or emergency intubation situations